Stanisław Lem the Player – An Inspiration by a Fictional Review of a Non-Existent Publication - Josef Krob (Profil, 2021)
Lem’s The Perfect Vacuum is a collection of reviews by fictional authors of non-existent scientific papers. This includes a lecture by Alfred Testa delivered on the occasion of the Nobel Prize in Physics. It is actually a recapitulation of a cosmological concept based on the discovery of a forgotten idea of Aristides Acheropoulos to explain the silentium universi. Why is the universe silent? Why does no one answer our calls sent to the interstellar distances? Why is our search for extraterrestrial civilizations unsuccessful? In his lecture, Testa layers before the audience the fundamental questions of the relationship between mathematics and physics, an interpretation of the latest discoveries of modern cosmology, and an explanation of the physical laws of relativity theory and quantum mechanics, including the metaphysical question of why they are just that. Because Lem sets before the reader a story of scientific discovery, the opportunity is offered to take it quite seriously, not as fiction but as science, and to look at its various components through the eyes of contemporary science.